2018
DOI: 10.1038/s41746-018-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and accurate deep learning with electronic health records

Abstract: Predictive modeling with electronic health record (EHR) data is anticipated to drive personalized medicine and improve healthcare quality. Constructing predictive statistical models typically requires extraction of curated predictor variables from normalized EHR data, a labor-intensive process that discards the vast majority of information in each patient’s record. We propose a representation of patients’ entire raw EHR records based on the Fast Healthcare Interoperability Resources (FHIR) format. We demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
1,326
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,850 publications
(1,457 citation statements)
references
References 76 publications
18
1,326
1
9
Order By: Relevance
“…Our prediction system is thus much more flexible and general, since it can be used with patients admitted for the first time with no known history. Second, [30] and [31] use deep neural network models whereas the current article presents results obtained with more classical models that: (i) perform faster on CPU machines, and (ii) are more intelligible: they offer more insights into the factors that influence the predictions, as emphasized in [32]. For instance, the weights computed by our models are stable and intelligible, allowing further interpretation (and fix if needed) by clinicians.…”
Section: Related Workmentioning
confidence: 90%
See 3 more Smart Citations
“…Our prediction system is thus much more flexible and general, since it can be used with patients admitted for the first time with no known history. Second, [30] and [31] use deep neural network models whereas the current article presents results obtained with more classical models that: (i) perform faster on CPU machines, and (ii) are more intelligible: they offer more insights into the factors that influence the predictions, as emphasized in [32]. For instance, the weights computed by our models are stable and intelligible, allowing further interpretation (and fix if needed) by clinicians.…”
Section: Related Workmentioning
confidence: 90%
“…Closely related works in terms of research objectives are the independent works performed simultaneously found in Avati et al [30], Rajkomar et al [31]. Authors develop a model for predicting all-cause mortality of patients from EHR data.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications of ML in the context of pharmaceutical research typically showcase algorithms trained on huge data sets that identify correlations between features predictive of a given outcome . A few highlights from the drug discovery and development pipeline in which ML methods have added value are predictions of ligand‐protein binding from chemical properties, automatic classification of biopsy images, and prediction of medical events from electronic health records …”
mentioning
confidence: 99%